Analysis of the Neurogenesis: Prepattern gene network сontrolling the first stage in Drosophila melanogaster bristle pattern development - D. P. Furman; T. A. Bukharina (Вавиловский журнал генетики и селекции)
The external insect chitinous skeleton is unable to respond to stimuli; the external signals are received by specialized receptors. Drosophila perceives the tactile stimuli by its external sensory organs, the microchaetes and macrochaetes residing on the head and back (notum). The microchaetes (hairs) are numerous and arranged in perfect rows along the body. The macrochaetes (bristles) are rather few and are strictly positioned on the head and notum, being referred to as bristle pattern. Bristles act as mechanoreceptors, providing balance for flying drosophila. The proper bristle pattern of an adult fly develops through several stages. Its basic stage is formation of prepattern for the future bristles, represented by proneural clusters. The proneural clusters separate from the ectodermal cells in imaginal discs in the third instar larvae and early prepupae. They are induced by prepattern factors, identified with the transcription factors driving expression of their target genes in certain disc regions. Reconstruction of the gene network controlling prepattern development and its analysis are for the first time described as well as the principles underlying arrangement and function of this network. The hierarchical structure of the network, its key components, and regulatory circuits are identified. The network comprises 80 entities interconnected via 109 regulatory interactions. The key objects of the network, displaying the greatest connectivity with its other components, are the ASC proneural proteins encoded by the achaete and scute genes, and the proteins Decapentaplegic (Dpp) and Wingless (Wg). The structure of the network is hierarchical and has at least three control levels. The network acts as a gene ensemble owing to coordinated functioning of the regulatory circuits controlling activities of the corresponding genes both within and between the levels. The resulting effect of the network operation consists in activation of the AS-C, proneural genes, the expression of which distinguishes the cells of proneural cluster from the surrounding ectodermal cells.